THE EFFECT OF HEALTH EDUCATION IN SURGERY PREPARATION TO ANXIETY LEVEL OF PATIENTS WITH PRE HERNIORRHAPHY IN RAA SOEWONDO HOSPITAL PATI - Mohamat Iskandar (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: RAA Soewondo Hospital Pati treated herniorrhaphy patients around 454 patients every year. The results of the preliminary study a study of 10 patients undergoing surgery herniorrhaphy through interviews revealed that most patients do not understand the circumstances that will be experienced, still worried by the operation, and yet ready to undergo surgery. Aims: The purpose of this study was to determine the effect of health education on surgery preparation to anxiety level of patient's with pre herniorrhaphy in RAA Soewondo hospital Pati. Method: This study used quasi-experimental design, One Group with Pretest and Posttest. Thirty patients were selected by accidental sampling with variables health education and level of anxiety patient pre herniorrhaphy. HARS (Hamilton Rating Scale For Anxiety) was employed as instrument for data analysis. Result: Twenty two respondents experienced moderate anxiety before health education. After health education, only 17 respondents experienced mild anxiety. Wilcoxon test obtained the mean difference of anxiety level before and after health education is 0.49 with a difference of standard deviation 0.077 and p-value 0.001 which mean there is a significant difference of anxiety level before and after health education. Conclusion: There is the influence of health education on the preparation procedure of surgery on the patient's anxiety level pre herniorrhaphy in hospitals RAA SoewondoPati. To reduce anxiety in patients with pre herniorrhaphy, expected that the comprehensive health education in patients with pre herniorrhaphy.